IRIGASI HEMAT AIR PADA PADI LOKAL DENGAN VARIASI KETEBALAN TANAH OLAH MENGGUNAKAN POLA TANAM SRI (SYSTEM OF RICE INTENSIFICATION) - Ludong, Daniel P.M.; Ai, Nio Song (Universitas Sam Ratulangi, 2016)
ABSTRACT The objective of this research was to evaluate the vegetative development in 3 North Sulawesi local rice varieties (Superwin (A), Temo (B) dan Burungan (C)) as a response to the thickness variation of cultivated soil layer combined with irrigation deletion. This research was conducted in the glasshouse using polyvinyl chloride (PVC) column (500 mm height, 125 mm diameter) as pots. The treatments consisted of 3 variations of cultivated soil layer, i.e. 18, 24 and 30 cm and the clay hardpan was placed below each of the cultivated soil layers. The level of irrigated water and the amount of the fertilizer were applied following the method of SRI (System of Rice Intensification). The results showed that reducing the thickness of cultivated soil layer to 18-24 cm saved the water as much as 6.15-8.12 L (29.7-39.2%) per pot compared with 30 cm thickness of soil layer in Burungan. Comparing with the 24 cm soil layer thickness, the treatments of 18 cm thickness saved 6.92 L (23.42%) and 5.77 L (18.32%) water, respectively in Superwin and Temo. Keywords: efficient irrigation, North Sulawesi local rice, System of Rice Intensification